Optimal Sampling Times for OIH-Clearance Calculations Using a Two-Compartment/Two-Sample Method - Koranda, P.; Lüscher, D.; Lourens, S.; Rösier, H. (Nuklearmedizin - NuclearMedicine, 1995)
Orthoiodohippurate (OIH) clearance data obtained with the two-compartment/two-sample method of Lear which uses varying sampling time combinations, were compared with those of the reference two-compartment/multi-sample method of Sapirstein. A total of 35 studies were performed in 33 adult patients. The OIH clearance values determined by the reference method ranged from 107 to 883 ml/min/1.73 m2, with a median of 406 ml/min/1.73 m2. It was ascertained that the precision of the Lear method is partially dependent upon the sampling time combination. The most reliable results with the Lear method in this patient population were obtained by taking a first sample at approximately 8 min p. L, and a second sample at 32 min p. i. or later.Die mit Hilfe der Zweikomipartiment/Zweiproben-Methode nach Lear bei verschiedenen Blutentnahmezeiten bestimmten Jod-Hippuran-Clearancewerte wurden mit jenen der Zweikompartiment/Multiproben-Methode nach Sapirstein verglichen. Insgesamt wurden 35 Studien bei 33 erwachsenen Patienten ausgewertet. Die mit der Zweikompartiment/Multiproben-Methode bestimmten OIH-Clearancewerte lagen im Bereich von 107 bis 833 ml/min/1,73 m2, mit einem Median von 406 ml/min/1,73 m2. Es wurde festgestellt, daß die Genauigkeit der Lear-Methode von den Zeitpunkten der Blutentnahme abhängig ist. Die besten Ergebnisse brachte sie, wenn die erste Blutentnahme 8 min und die zweite 32 min p. i. (oder später) erfolgte.
Keywords: Radionuclide studies; quantitative renal function; orthoiodohippurate clearance; effective renal plasma flow